Pengaruh Produk dan Harga Terhadap Keputusan Konsumen Dalam Membeli Produk - Sri Wanti Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The aim of this research is to find out and analyze the various factors that influence consumer decisions in purchasing products. In this research, researchers carried out a quantitative associative approach. Associative research is research that aims to determine the influence or relationship between two or more variables. Data analysis is statistical in nature with the aim of testing research hypotheses that have been applied previously. The population in this study were all consumers who bought shoe products at JCT Medan City with a sample of 20 consumers taken at random. The data collection technique in this research is by using a questionnaire. And the data analysis technique used is to carry out simple regression analysis. In this research, the multiple linear regression analysis method uses SPSS 22 software. The results of this research are that purchasing factors have a significant influence on consumer decisions. The product has no influence on consumer decisions. Meanwhile, purchasing factors and products together influence consumer decisions in purchasing products. It can be seen that the calculated t value for the variable product purchasing factors (X1) is 2.337 > t table 2.093 and the significant value is 0.005 < 0.05, so ha is accepted and ho is rejected. Meanwhile, t is calculated for the product variable (X2) with a value of t = 2.612 < ttable = 2.093. So the decision is that Ha is accepted and Ho is rejected.